Bone Gap - Ruby, Laura (New York Balzer & Bray, 2015)
Eighteen-year-old Finn, an outsider in his quiet Midwestern town, is the only witness to the abduction of town favorite Roza, but his inability to distinguish between faces makes it difficult for him to help with the investigation, and subjects him to even more ridicule and bullying.
Keywords: Kidnapping; Face perception; Interpersonal relations; Bullying; Brothers; Juvenile works; Fiction